STUDENT MANUAL : TESTING A HYDROCARBON REFRIGERANT LEAK DETECTOR WITH ARDUINO NANO AND MQ-2 SENSOR - Akhsan, Ibnu Nur; Wibawa, Basuki (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2024)
This research aims to address public concerns regarding the use of hydrocarbon refrigerants, which are prone to leakage and have the potential to cause explosions and fires. Therefore, a hydrocarbon refrigerant gas leak detector was developed using the MQ-2 sensor for accurate detection. This device utilizes an Arduino Nano microcontroller to detect the gas. The manufacturing method includes both hardware and software development. The results show that this device is effective in detecting leaks by measuring the PPM (parts per million) values from five sensors, producing 70 buzzer sounds in 20 minutes when 105 grams of hydrocarbon refrigerant is released, and the device tsemperature reaches 30°C. The visual indicator provides "safe" and "leak" statuses at a pressure of 130 Psi, and the light indicator remains on during testing. In conclusion, this device improves the maintenance procedures of hydrocarbon refrigerants in refrigeration systems, giving users peace of mind because leaks can be detected with sound and visual indicators every 17 seconds.